Africanidades em três letras de rap de Rincon Sapiência: fuga como resistência, tradição oral e consciência - Santos, Wellington Alves dos (2019)
The present study identifies and analyzes cultural, behavioral, resistance, self esteem and other elements; as well as literary aspects and the exposure of the art, religion, beauty and great achievements of the Afro people, present in three rap compositions of Rincon Sapiência, such as the legends of African traditions, the inherited elements from African ancestry; while examining them comparatively with other artistic productions, but with the same discursive content. The focus is on the lyrics of the rapper's "Crime bárbaro”", "Ponta de lança (Verso livre)" and "Amores às escuras". The study considers the oral tradition, which is so important for the memory and identity of the peoples of Africa, as the main influence mark of the resistance movements of the Brazilian black people, in most cases centered on the spoken word, such as literary sarahs, slams poetry, educational practices and rap itself. The starting point of the work seeks to situate aspects of African matrix and their contributions in the Brazilian peripheral cultural production; passing also by the emergence, trajectory and performance of rap in Brazil. The study also denounces the actions of exclusion of the black people in the formation of speeches, mainly literary, by the hegemonic elites; proposing a new look at the artistic expressions developed in the peripheries of the country. The study seeks to highlight from the selected lyrics the potential of rap discourses in the construction of self - esteem and affirmation of descendants of the African diaspora; thus awakening the desire to be protagonists and writers of their own stories. In this sense, peripheral art is the escape element of the marginalized against the violence suffered. The work is based on theorists such as Amadou Hampaté Bâ, Jan Vansina, Paul Zumthor, Eduardo de Assis Duarte, Jessé Souza, Domício Proença Filho, Jorge Nascimento, among others.